Efeito do óleo da espécie vegetal Caryocar villosum em linhagem de células vero in vitro - LOPES, Izabella Carla Silva (Universidade Federal do Pará, 2025)
Fibroblasts are cells that participate in different processes in the body, being indispensable in the development and homeostasis of tissues. They are important agents in the healing process, being present in the inflammatory, proliferative and remodeling phases. These cells produce biomolecules that constitute the extracellular matrix, such as collagen, which provide the necessary support for healthy healing. However, healing is a complex process, and it is proneto failure, so it´s important to investigate therapeutic alternatives to produce more effective treatments in cases where natural healing is not effective. Natural products from plants are widely used as therapeutic forms for healing considering their lower side effects, low cost, this combined with traditional knowledge makes it attractive to studies that prioritize valuing biodiversity. Caryocar villosum (Cv), a fruit native to the Amazon region, is a remarkable source of bioactive compounds with therapeutic potential that has cosmetic and pharmaceutical applications. In this work, the action of Cv oil (CvO) on VERO cell line (fibroblast-like cells)was investigated. The cells were treated with 75, 125 and 250 μg/mL for 24 hours. Cytotoxicity assays, optical microscopy, cell proliferation, morphological analysis, and analysis of extracellular matrix components, such as phalloidin staining and immunofluorescence for type III collagen antibody, were performed. Any cytotoxicity was observed in the cells after CvOtreatment. CvO treatment induced morphological and physiological changes in the cells indicating cell activation. Fluorescence microscopy revealed greater cell spreading, rearrangement of actin filaments and increased cell surface exposure compared to untreated cells. Furthermore, this study suggests that fibroblasts treated with CvO are activated through cytoskeletal rearrangement, increasing cell surface, proliferating, and increasing collagen synthesis. These findings indicate that CvO may be a good therapeutic strategy from biodiversity to stimulate the healing process.